Relationship between socioeconomic status and accessibility for endoscopic resection among gastric cancer patients: using National Health Insurance Cohort in Korea: poverty and endoscopic resection - Kim, Na Yeon; Oh, Jun Seok; Choi, Young; Shin, Jaeyong; Park, Eun-Cheol (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2017)
Background Gastric cancer is one of the most common types of cancer among patients in Korea. We measured the inequity in accessibility to endoscopic mucosal/submucosal resection (EMR) for early and curable gastric cancer treatment among different income classes in patients diagnosed from late 2011 to 2013. Methods Data were obtained from the National Health Insurance Cooperation Claim Data from patients diagnosed from late 2011 until the end of 2013, to provide a total of 1,671 patients with newly diagnosed carcinoma in situ of gastric and gastric cancer among 1,025,340 enrollees. Multiple logistic regression analysis was conducted to investigate the associations between independent variables and the rate of treatment with EMR. Results Among 1671 gastric cancer patients, 317 (19.0 %) subjects were treated with EMR. The ‘lowest’ income group was associated with a statistically significant lower rate of EMR treatment [odds ratio (OR) = 0.55, 95 % confidence index (CI) 0.34–0.89] compared to the ‘highest’ income group. The ORs for the ‘low-middle’ and ‘middle-high’ income groups were both higher than for the reference group, although these were not significantly different. According to the subgroup analysis by gender, rate of EMR treatment of ‘lowest’ income group (OR = 0.37, 95 % CI 0.18–0.74) was significantly lower only among men. Conclusion In conclusion, we suggest that although universal health insurance in Korea has covered EMR treatment since August 2011, patients from the lowest income group are less likely to receive this treatment. Thus, we need to detect more eligible early-stage gastric cancer and treatment for individuals of low socioeconomic status.